The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016 18th International Conference on Transparent Optical Networks (ICTON) 2016
DOI: 10.1109/icton.2016.7550488
|View full text |Cite
|
Sign up to set email alerts
|

25 Gbps mobile visible light communication system employing fast adaptation techniques

Abstract: Visible light communication (VLC) systems have typically operated at data rates below 20 Gbps and operation at this data rate was shown to be feasible by using laser diodes (LDs), beam steering, imaging receivers and delay adaptation techniques. However, an increase in the computational cost is incurred. In this paper, we introduce fast computer generated holograms (FCGHs) to speed up the adaptation process. The new, fast and efficient fully adaptive VLC system can improve the receiver signal to noise ratio (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 16 publications
(32 reference statements)
0
14
0
Order By: Relevance
“…Thus, the achieved SINR values yields data rates between 50-60 Mbps. As discussed earlier, recent literature [25,27] has shown that RGB-LDs can generate white light that has comparable properties with white LED sources. The modulation bandwidth of such RGB-LDs can be multiple GHz and hence can provide multi-Gbps data rate while maintaining SINR ≥ 20dB for θ d < 60 o .…”
Section: Appropriate Number Of Photo-detectorsmentioning
confidence: 84%
See 1 more Smart Citation
“…Thus, the achieved SINR values yields data rates between 50-60 Mbps. As discussed earlier, recent literature [25,27] has shown that RGB-LDs can generate white light that has comparable properties with white LED sources. The modulation bandwidth of such RGB-LDs can be multiple GHz and hence can provide multi-Gbps data rate while maintaining SINR ≥ 20dB for θ d < 60 o .…”
Section: Appropriate Number Of Photo-detectorsmentioning
confidence: 84%
“…It has been shown in [26,27] that a combination of visible RGB lasers along with a diffuser can generate white light that has comparable properties with white LED sources. [25] has shown that data rates of as high as 25Gbps can be achieved using RGB-LDs.…”
Section: A Visible Light Communicationmentioning
confidence: 99%
“…Using linearization Equations (8)(9)(10)(11) to replace the first part of Equation 7, Equation 7can be re-written as follows: The MILP model is subject to three constraints as follows:…”
Section: Milp Modelmentioning
confidence: 99%
“…Optical wireless communication (OWC) systems have been posited as a potential solution for supporting multiple-users and high data rates, and is considered to be part of the sixth generation (6G) of communication systems. Recently, OWC systems have gained the interest of many researchers [2] - [8] because they can provide higher capacity and better security compared to RF systems [3], [4]. Moreover, OWC systems have been widely shown to support high data rates of up to 25 Gbps in indoor environments [4]- [13].…”
Section: Introductionmentioning
confidence: 99%